Label-free creatinine optical sensing using molecularly imprinted titanium dioxide-polycarboxylic acid hybrid thin films: a preliminary study for urine sample analysis - Lee, Seung-Woo; Ahmed, Soad; Wang, Tao; Park, Yeawon; Matsuzaki, Sota; Tatsumi, Shinichi; Matsumoto, Shigekiyo; Korposh, Sergiy; James, Stephen W. (MDPI, 2021)
Creatinine (CR) is a representative metabolic byproduct of muscles, and its sensitive and selective detection has become critical in the diagnosis of kidney diseases. In this study, poly(acrylic acid) (PAA)-assisted molecularly imprinted (MI) TiO2 nanothin films fabricated via liquid phase deposition (LPD) were employed for CR detection. The molecular recognition properties of the fabricated films were evaluated using fiber optic long period grating (LPG) and quartz crystal microbalance sensors. Imprinting effects were examined compared with nonimprinted (NI) pure TiO2 and PAA-assisted TiO2 films fabricated similarly without a template. In addition, the surface modification of the optical fiber section containing the LPG with a mesoporous base coating of silica nanoparticles, which was conducted before LPD-based TiO2 film deposition, contributed to the improvement of the sensitivity of the MI LPG sensor. The sensitivity and selectivity of LPGs coated with MI films were tested using CR solutions dissolved in different pH waters and artificial urine (near pH 7). The CR binding constants of the MI and NI films, which were calculated from the Benesi–Hildebrand plots of the wavelength shifts of the second LPG band recorded in water at pH 4.6, were estimated to be 67 and 7.8 M−1, respectively, showing an almost ninefold higher sensitivity in the MI film. The mechanism of the interaction between the template and the TiO2 matrix and the film composition was investigated via ultraviolet–visible and attenuated total reflectance Fourier-transform infrared spectroscopy along with X-ray photoelectron spectroscopy analysis. In addition, morphological studies using a scanning electron microscope and atomic force microscope were conducted. The proposed system has the potential for practical use to determine CR levels in urine samples. This LPG-based label-free CR biosensor is innovative and expected to be a new tool to identify complex biomolecules in terms of its easy fabrication and simplicity in methodology.
Keywords: urine analysis; long period grating; TiO2 nanothin film; creatinine; molecular imprinting; liquid phase deposition